Improving the corrosion behaviour of Zn-Ni alloy coatings on 316 SS from chloride-sulfate bath by addition of triethanolamine or sucrose - Alfalah, Mothana Ghazi Kadhim; Abbar, Ali H.; Kandemirli, Fatma (International Association of Physical Chemists (IAPC), 2025)
Corrosion of Zn-Ni alloy coatings on stainless steel 316 SS in a chloride-sulfate bath with the addition of either triethanolamine or sucrose was examined. A constant cathode potential was used to deposit zinc-nickel alloys, while cyclic voltammetry and potentio-dynamic polarization were used to measure corrosion. In addition, scanning electron microscopy was utilized to analyse Zn-Ni alloy coating surface layers formed with¬out and with additives. The outcomes discovered that the corrosion resistance of Zn-Ni alloy coat¬ings in 3.5 % NaCl solution was highly influenced by adding triethanolamine or sucrose. Decreasing the Zn:Ni molar ratio led to an increase in corrosion resistance. All Zn-Ni alloy coatings were superior to pure Zn coating in their corrosion behaviour. The best result was found for potentiostatic electrodeposition of Zn-Ni alloy at the cathodic potential of -1.3 V vs. Ag/AgCl for 20 minutes in the presence of 0.335 M triethanolamine from a solution containing 0.02 M ZnCl2, 0.1 M NiSO4, 0.4 M H3BO4 and 1 M Na2SO4. For this Zn-Ni coating, a low corrosion rate of 0.00795 mm year-1 was observed at Ecorr = -0.5 V vs. Ag/AgCl and icorr= 0.535 µA cm-2. Scanning electron microscopy confirmed that this alloy has a granular structure with no cracks and a less porous structure. The new Zn-Ni alloy is superior in its properties in terms of corrosion resistance compared with those obtained in previous studies.
Keywords: organic additives; Sucrose; Chemistry; corrosion resistance; Metal alloy coatings; Triethanolamine; SEM; electrodeposition; Corrosion resistance; Zn-Ni alloy; bath composition; Electrodepositing; QD1-999